Experimental Investigation on Effect of Ingot Processing on Gear Bending Fatigue Performance - Wu Zhongrui; Wei Peitang; Chen Difa; Mao Tianyu; Liu Huaiju (Jixie chuandong)
Ingot processing affects gear fatigue performance, which remains to be studied and becomes an important bottleneck problem limiting gear anti-fatigue design and cost saving. Surface integrity measurements of 18CrNiMo7-6 gears with mold ingots, continuous casting billet and electro-slag ingots are carried out, and tooth root residual stress, surface roughness and hardness gradient of these gears are studied. Based on GB/T 14230—2021 Test method of tooth bending strength for gear load capacity, gear bending fatigue tests are conducted with the staircase method. The bending fatigue limits under different reliabilities are obtained, and the influence of ingot processing on the bending fatigue performance is explored. The gear bending fatigue limit is also evaluated with the effective Locati method, and is compared with results of the lifting method. It provides some references for fundamental data construction of gear fatigue and anti-fatigue design in China.